1954
DOI: 10.1042/bj0580486
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of serine and Leuconostoc citrovorum factor by cell suspensions of Streptococcus faecalis R

Abstract: The term folic acid will be used throughout in general reference to the group as a whole; individual members will be named specifically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1959
1959
1975
1975

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The qpthesis of citrovorum factor by suspensions of Leuconostoc mesenteroides P60 variant strain Lascelles & Woods (1954) showed that during the synthesis of serine from glycine and formate by suspensions of Streptococcus faecal& R, there was a concurrent formation of a factor or factors active for the growth of L. citrovorum. A similar appearance of this factor attended the production of serine by suspensions of L. mesedmoides P 60; glucose, formate and p-aminobenzoic acid were essential substrates ( Table 1; .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The qpthesis of citrovorum factor by suspensions of Leuconostoc mesenteroides P60 variant strain Lascelles & Woods (1954) showed that during the synthesis of serine from glycine and formate by suspensions of Streptococcus faecal& R, there was a concurrent formation of a factor or factors active for the growth of L. citrovorum. A similar appearance of this factor attended the production of serine by suspensions of L. mesedmoides P 60; glucose, formate and p-aminobenzoic acid were essential substrates ( Table 1; .…”
Section: Resultsmentioning
confidence: 99%
“…Carbon dioxide has the dual capacity of stimulating serine synthesis (Lascelles et al 1954;Cross, 1960) and of preventing leucovorin inactivation by Leuconostoc mesenteroides P 60. Any hypothesis about a relationship between these two activities would be supported if another compound which produced one of the phenomena also produced the other.…”
Section: The Replacement Of Cog By ~S C O T~j~c Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponded to a 60-fold increase for strain Hfm growing in the absence of thiamin, but cultures of the other mutants increased by only seven-to tenfold during vitamin deprivation. Streptococcus faecalis was grown without aeration in medium G (Lascelles & Woods, 1954) modified by the addition of folic acid (0.1 mg/l), DL-IIPOIC acid (40pg/l) and either pyridoxal hydrochloride (0-2 mg/l) or DL-alanine (0.2 g/l) when vitamin €3,-deficient organisms were required. This organism was also grown in foIic acid assay medium (Difco) with added DL-lipoic acid (40 pgll) and either folic acid ( I mg11) or the following replacement mixture (mg/l) for preparing folate-deficient bacteria : thymine (50), adenine (I o), guanine ( IO), L-serine (ZOO), and L-methionine (200) according to Samuel, D'Asi & Rabinowitz (1970).…”
Section: E T H O D Smentioning
confidence: 99%
“…Teltrahydro,folic acid + CH2OH-CH (NH..) -COOH =CH2 (NH2) COOH + 5N10N, methylene tetrahydrofolic acid This enzyme has been highly ipunified from bacterial (7,19) and animal sources (12). Evidence for a similar reaction in higher plants was obtained from in vivo experiments in which radioactive glycine or compounds easily converted to glycine such as glycollate were infiltrated into plant sections and the formation of radioactive serine observed (9,16,17).…”
mentioning
confidence: 99%